Promoting Interaction in the English Classroom Through the Designing of Board Games With Sixth Graders at a Public School (2017)
ABSTRACT: This action research project was done with the intention to explore to what extent it is possible promoting interaction in the English classroom through the Designing of Board Games with Sixth Graders at a Public School. This implementation has been carried out in a public school in Medellin with 37 students from 6th grade. The steps of the implementation were building vocabulary with the students, play board games as example. Construction of the material including: questions board and specific mechanics. Finally playing and date collection analysis. The analysis of the date suggests that board games can provide great opportunities for students’ interaction with a purpose in the English classroom, as well as a great conductor to integrate different topics.